Assurance of seafood quality - Huss, H.H (FAO, 1994)
This document is primarity focused on the application of the Hazard Analysis Critical Control Point ( HACCP) system to the fish industry. The document reviews in detail the potential haxards the utilization of HACCP in different types of fish industries.